Real‐life assessment of chronic obstructive pulmonary disease patient performance with different inhalers. Issue 4 (18th December 2020) - Harb, Hadeer S.; Ibrahim Laz, Nabila; Rabea, Hoda; Abdelrahim, Mohamed E. A.
Abstract: Purpose: This study aimed to evaluate handling of six common inhalers and to determine correlations between correct inhaler technique and patient demographics/ clinical variables. Methods: A total of 180 chronic obstructive pulmonary disease (COPD) patients were crossed‐over to handle their past‐experienced inhalers among (pMDI, Aerolizer, Handihaler, Breezhaler, Turbohaler, and Diskus) randomly, without receiving verbal or demonstrative instruction (baseline assessment). Inhaler technique was assessed using previously defined checklists. The correct use of the inhaler was then demonstrated and the patient was evaluated for inhaler use again. Demonstration was repeated until a correct technique was achieved. Number of counselling attempts needed to a complete right handling, patient demographics and clinical variables were recorded. Results: The mean percentage of total correct steps showed that pMDI is significantly lower than all other inhalers (76.01 ± 12.61 vs 84.18 ± 10.87, 84.60 ± 12.10, 85.91 ± 9.82, 90.63 ± 9.29 and 91 ± 10.22 for Diskus, Turbohaler, Aerolizer, Handihaler and Breezhaler, respectively, at P < .001). Breezhaler showed the lowest percentage of participants with at least 1 critical error (20%) however, pMDI showed the highest percentage (85.19%) at P < .05. Breezhaler showed that the highest percentage of participants achieved a complete right handling after 1st counselling attempt, however, pMDI was the only inhaler included in a 3rd and 4th counselling attempts (5.93% and 0.74%, respectively). Weak and very weak correlations were found between total correct steps and demographics/clinical variables. Conclusions: pMDI is not preferable for handling by COPD patients. DPIs vary in ease of use, so that inhaler therapy must be individualised on basis of patient handling assessment with repeated counselling.